Rola psychiki ucznia w kształceniu nawyków prawidłowej emisji głosu solowego na etapie szkoły muzycznej II stopnia = The role of the student's psyche in developing habits of proper solo voice emission at the stage of the 2nd degree music school - Majzner, Rafał (Kraków ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The author discusses the conditions for proper voice emission in classical singing, proposing that they should include the student?s psyche. He emphasizes the importance of the student?s optimistic attitude to exercises and public performances, which determines the sense of self-efficacy and the assessment of the situation that allows the student to avoid stressful events and to direct them on mobilizing the body in a crisis.
Keywords: śpiew klasyczny; warunki dobrej emisji głosu; psychika; poczucie skuteczności; trema; classical singing; conditions of proper voice emission; psyche; sense of self-efficacy; stage fright